Dynamics of self-similar pulse generated in normal dispersion-decreasing fiber. (March 2015) - Xia, Ge; Feng, Youceng
Abstract: Self-similar pulse can be generated in a normal dispersion-decreasing fiber. We show that the dynamics of self-similar pulse evolution is governed by the different spectrum broadening mechanisms in the different stages, which is confirmed by the typical pulse spectral structures with amplitude noise added.